Legal Framework of Developing Corporate Governance in Healthcare Organizations in Kazakhstan - SAKTAGANOVA, Indira Sovetovna; SAKTAGANOVA, Gulmira Sovetovna; ORMANOVA, Sholpan Sherehanovna; ASHIMOVA, Elnara Ashimovna; SAULEN, Nurzhan (Journal of Advanced Research in Law and Economics, 2019)
One of the important tasks set by the Head of State in 100 Concrete Steps to Implement Five Institutional Reforms , the Plan of the Nation, is step 81 – Development of Private Medicine, Implementation of Corporate Governancein Medical Organizations . The development of private medicine and the improvement of independence of state healthcare organizations through a gradual transition to the status of state-owned enterprises on the basis of the right of economic management with the introduction of corporate governance set new requirements to senior managers of healthcare organizations, the nature of their tasks and ways to solve them. In order to implement the project of the Ministry of Health of the Republic of Kazakhstan (RK) ‘Development of Management and Corporate Governancein Healthcare Organizations’, the transition of state medical organizations on the basis of economic management has been analyzed. The methodological and advisory support is provided to medical organizations at the regional level. The regulatory framework in the area of management and corporate governance of healthcare is developed and amended. The activities of the supervisory boards of state-owned enterprises (SE) on the basis of the right of economic management (REM) have been analyzed and estimated. The data on the current secretaries of the supervisory boards and independent members of the supervisory board have been collected. The corporate governance in subordinate organizations has been rated. The rating of corporate governance is becoming an indicator of compliance with the best practices, both in state-owned and private organizations around the world. Such estimation makes it possible to analyze not only the mechanisms of work, but also to understand the dynamics of these processes. Using the in-depth approach, this instrument helps determining the potential and considerablyimproving the efficiency of the supervisory boards and the entity, as a whole.